Tax Evasion and its Effect on Criminal Liability under UAE Tax Law - المنصورى، حمود خليفة (جامعة الإمارات العربية المتحدة - كلية القانون, 2019)
يتناول البحث التالي تحليل نقدي لمسألة أساسية وهي التهرب من دفع الضرائب، من خلال تبيان لمفهوم التهرب الضريبي، والعوامل التي من المرجح أن تؤدي إلى مثل هذه التهربات، وكذلك آثار عمليات التهرب الضريبي على البلد واقتصاده. كما تتطرق الدراسة إلى تحليل تأثير عمليات التهرب الضريبي على المسؤولية الجنائية في دولة الإمارات العربية المتحدة على وجه الخصوص، ولتحقيق ذلك تم تناول كيفية أساليب القيام بعملية التهرب الضريبي وتأثيره على دولة الإمارات العربية المتحدة واقتصادها من خلال ذلك التهرب. التهرب الضريبي هو عمل غير قانوني، وغالباً ما يحاول الأفراد والمنظمات عن طريق أعمال غير قانونية، عدم دفع الضرائب المستحقة عليهم. إن الأعباء الضريبية والتنفيذ غير الفعال للوائح ونوايا توفير الأموال للمصالح والنفقات الشخصية، هي بعض العوامل التي تجعل الأفراد أو المنظمات تتهرب من دفع الضرائب، والتي من المفترض أن تضاف هذه الضرائب التي يتم التهرب منها إلى اقتصاد البلد. فيما يتعلق بدولة الإمارات العربية المتحدة، يبين لنا من خلال الدراسة أن لديها سياسات ضريبية متساهلة مع عدم وجود ضريبة دخل على الأفراد، ومخططات ضريبية خاصة للشركات التي تعمل في البلاد، حيث العدد الكبير منها هي شركات أجنبية تعمل من خلال مناطق التجارة الحرة في البلاد. أدخلت دولة الإمارات العربية المتحدة مؤخراً قوانين ضريبية جديدة في عام ٢٠١٧، والتي تهدف إلى تطبيق أكثر صرامة للسياسات والمدفوعات الضريبية في الدولة. مع وضع القانون الجديد، يمكن توقع أن تتحكم الدولة في مدفوعاتها الضريبية بشكل أكثر فعالية، ولكن هناك حاجة لتطبيق سياسات رقابة صارمة وسياسات نقدية.
The following research presents an analysis reflecting on a key issue namely tax evasion. The study reflects an understanding on the concept of tax evasion, the factors that are most likely to result in such evasions, as well as the impacts of such evasions on a country, its people, and its economy. The study analyses the effect of such tax evasions on the criminal liability of the UAE, in specific, and to achieve this, the theoretical understanding and reviews on the concept have been done to effectively understand how evasion works and affects UAE and its economy in the process. The study has been accomplished based on a secondary research method, where text books, researched journals, news reports, and other online researched articles and publications have been used to conduct the study. The research has been presented systematically, discussing the concept of tax evasion in the beginning, following which gradually, the types of tax evasion, the risks related to such evasions, the reasons and impacts of evasion in a country, the effects on a country’s economy, have been discussed. Tax evasion is an illegal act that often individuals and organizations attempt, by means of illegal acts, in order not to pay for their due taxes. Tax burdens, ineffective implementation of regulations, and the intentions to save funds on one’s own self for self-interests and expenses, are some of the factors that cause individuals and/or organizations to evade their taxes. The impacts of tax evasion could be obtained as being extremely negative on the overall economy and growth of a country. Taxes that are evaded are supposed to add to the economy of a country. With regards to UAE, it could be obtained from the study that UAE has lenient tax policies, with no income tax on individuals, and special tax schemes for the companies that operate in the country, particularly implying the large number of foreign companies that operate through the free trade zones of the country. The European Union has presented a note of concern for the UAE, along with listing the country on the list of tax havens, stating that the companies that operate in the free trade zones are not necessarily making payments for their taxes, and hence indulging in tax evasions. The country has recently introduced its new tax laws in 2017, which targets stricter implementation of tax policies and payments in the UAE. This has been found to be a key attempt of the country towards preventing tax evasion possibilities in the country, which otherwise could result in increased criminal liability for the country. With the new law being established, the country can be expected to control its tax payments more effectively, however there is a need to implement strict supervision and monetary policies.
Keywords: التهرب الضريبي -- قانون الضرائب الإماراتي -- الأعباء الضريبية -- السياسة الضريبية